Examining The Relationship Between Self-Efficacy and Speaking Proficiency: A Correlational Study Among English Major Students - Delis Meta Tiana; Aprillia; Rina Lestari; Lidya Damayanti (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research investigates the correlation between the EFL learners’ self-efficacy and speaking proficiency. Considering speaking as essential but problematic language competency, the study in question looks at the impact of self-efficacy on students’ proficiency in accomplishing speaking tasks with confidence and efficiency. The study utilized a quantitative correlational technique and comprised 35 second-semester students from a private university in Jakarta. Data were gathered using a self-efficacy questionnaire and speaking performance evaluations focusing on pronunciation, grammar, vocabulary, fluency, and comprehension. The findings demonstrated a strong positive correlation (r = 0.796), the value of Sig. = 0.000 < 0.05 between students' self-efficacy and their speaking proficiency, indicating that elevated self-efficacy correlates with enhanced speaking proficiency. The results underscore the necessity for students to cultivate confidence and participate actively in speaking exercises.